Current practice of bedside teaching in undergraduate medical education of Bangladesh - Sultana, Jobaida; Ara, Iffat; Talukder, Humayun Kabir; Khan, Md Manir Hossain (Bangladesh Journal of Medical Education, 2017)
Introduction: Bedside teaching is the cornerstone of clinical teaching for the health professions. Different strategies have emerged to make it more effective. Many of the environments and opportunities available for bedside teaching and learning have changed. Methodology: This was a descriptive type of cross sectional study conducted in seven (three public and four private) medical colleges in Bangladesh over a period from July 2012 to June 2013 to determine the ways of conduction of bedside teaching in undergraduate medical education of Bangladesh. Total 30 Bedside teaching (BST) sessions conducted in the ward in Obstetrics and Gynaecology departments were observed by researcher herself and data was collected in a structured check list by using 5 points rubric (1-lowest quality, 5-highest quality). The checklist had four main sections- physical environment of bedside sessions, issues regarding patient's comfort and attitude towards patient, teaching tasks and group dynamics. Each section had a number of items and total 27 items were observed. For each variable frequency distribution, mean score and standard deviation (SD) were calculated.Here mean score 5- no need of further improvement, as it covered all the required criteria, 4- very minimum effort, 3- some effort, 2= moderate effort, 1= considerable efforts are needed to fulfill the required criteria. Result: Among physical environment factors the mean score of temperature, noise, space, teacher-student ratio were >2 but <3 and for light the mean score was >3 but <4. Among the issues regarding patient's comfort and attitude toward patient the mean scores on introducing everyone to the patient, maintaining privacy, explaining findings to the patient, genuine encouraging closure were >1 but <2 and on taking consent from the patient, showing appropriate attitude toward patient, teaching based on data about that patient were >2 but <3. Among teaching tasks the mean score on supervision of student during history taking, giving chance to practice the skills of the session, summarizing the session were >1 but <2 and on selection of the patient, supervision of student during physical examination, giving feedback, acting as a role model in physician- patient interactions, duration of the classes were >2 but <3 and on assisting a student during practicing a skill when needed, asking students to apply clinical reasoning skills were >3 but <4. Among group dynamics the mean score on active participation of the students and setting tasks for individual student were >1 but <2 and on setting goals for the group at the beginning of the class and setting time limit for every task were >2 but <3 and on active participation of the patients were >3 but <4. Conclusion: In all aspects of bed side teaching minimum to considerable efforts are necessary to make it more effective. A bedside teacher must know the importance of comfortable physical environment in learning and must learn how to involve patients and learners in the educational process, so faculty development is essential. Bangladesh Journal of Medical Education Vol.4(1) 2013: 2-7